2014
DOI: 10.1186/1471-2458-14-261
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity during the transition from primary to secondary school in Belgian children: what is the role of the school environment?

Abstract: BackgroundKey life periods have been associated with changes in physical activity (PA). This study investigated (1) how PA changes when primary school children transfer to secondary school, (2) if school environmental characteristics differ between primary and secondary schools and (3) if changes in school environmental characteristics can predict changes in PA in Belgian schoolchildren. Moderating effects of gender and the baseline level of PA were investigated for the first and third research question.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
4
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 46 publications
6
75
4
4
Order By: Relevance
“…Alternative data sources were consulted in case information on selected indicators was not available in the FCS, including the ToyBox study (4-6 years; n = 1327 for Flanders), 22 the 2013-2014 Health Behaviour in School-aged Children study (11-18 years; n = 9566 for Flanders, n = 14,180 for Wallonia), 23 the ENERGY study (10-12 years; Flanders; n = 1003 for adolescents, n = 763 for parents), 24 the 2012 Indicator Survey on health policies and regulations within schools (Flanders: n = 1006 for primary schools, n = 451 for secondary schools), 25 a regional survey on the importance given to PA promotion in secondary schools of French-speaking Belgium performed by the University of Liege (n = 51 secondary schools), 26 and a longitudinal study on the environment and PA of Flemish adolescents conducted by Ghent University (13-14 years at follow-up; n = 420). 27 Following selection of indicators, appropriate data sources, and items within those data sources, indicators were graded using the grading framework formulated by Active Healthy Kids Canada [A = 81% to 100%; B = 61% to 80%; C = 41% to 60%; D = 21% to 40%; F = 0% to 20%; INC (incomplete) = not enough valid/representative data available for grading]. 13 For each of the 11 indicators, sub-indicators for different age groups were graded according to this framework and an overall grade was established based on consensus among members of the RWG and endorsement from the stakeholder groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative data sources were consulted in case information on selected indicators was not available in the FCS, including the ToyBox study (4-6 years; n = 1327 for Flanders), 22 the 2013-2014 Health Behaviour in School-aged Children study (11-18 years; n = 9566 for Flanders, n = 14,180 for Wallonia), 23 the ENERGY study (10-12 years; Flanders; n = 1003 for adolescents, n = 763 for parents), 24 the 2012 Indicator Survey on health policies and regulations within schools (Flanders: n = 1006 for primary schools, n = 451 for secondary schools), 25 a regional survey on the importance given to PA promotion in secondary schools of French-speaking Belgium performed by the University of Liege (n = 51 secondary schools), 26 and a longitudinal study on the environment and PA of Flemish adolescents conducted by Ghent University (13-14 years at follow-up; n = 420). 27 Following selection of indicators, appropriate data sources, and items within those data sources, indicators were graded using the grading framework formulated by Active Healthy Kids Canada [A = 81% to 100%; B = 61% to 80%; C = 41% to 60%; D = 21% to 40%; F = 0% to 20%; INC (incomplete) = not enough valid/representative data available for grading]. 13 For each of the 11 indicators, sub-indicators for different age groups were graded according to this framework and an overall grade was established based on consensus among members of the RWG and endorsement from the stakeholder groups.…”
Section: Methodsmentioning
confidence: 99%
“…27 Furthermore, 91% and 90% of adolescents did not report that in their neighborhood there was so much traffic in nearby streets that it was dangerous to walk or cycle. Finally, 28% of adolescents reported that it was safe to play on the street in their neighborhood.…”
Section: Community and The Built Environment: Incmentioning
confidence: 99%
“…Lifestyle interventions could, therefore, be used to target improvements in HRQoL (Gillison, Standage, & Skevington, 2008). There is a known reduction in engagement in healthful behaviours, such as physical activity, during the school transition period making it particu-larly important to examine within this population (De Meester, Van Dyck, De Bourdeaudhuij, Deforche, & Cardon, 2014;Knowles, Niven, & Fawkner, 2011). More sensitive information about the association of different components of HRQoL with physical activity would help to inform more effective development of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Estos cambios atienden ineludiblemente al proceso de maduración que se produce en la transición de la etapa de Primaria a Secundaria, no sólo en la esfera personal (Isona, Navia y Felpeto, 2013), sino también en el plano situacional y ambiental (De Meester, Van Dyck, De Bourdeaudhuij, Deforche, y Cardon, 2014 En segundo lugar, el estudio analizó la influencia del género, del deporte practicado y del nivel de práctica deportiva en cada una de las etapas. En relación con el género, los resultados no mostraron diferencias significativas en Primaria y sí en Secundaria, en favor de los varones.…”
Section: Discussionunclassified
“…En el ámbito personal se ha puesto de manifiesto la necesidad de autonomía, independencia, autodeterminación e interacción social (Isona, Navia y Felpeto, 2013). Además, en numerosos países coincide con la incorporación del estudiante a un nuevo centro educativo, que comporta notorios cambios situacionales y ambientales (De Meester, Van Dyck, y De Bourdeaudhuij, 2014).…”
Section: Introductionunclassified